Pemberdayaan Ekonomi Masyarakat Berbasis pada Wirausaha Keluarga Mandiri di Kelurahan Geluran Sidoarjo - Rosyafah, Siti; Tri Lestari; Budi Rianto (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2024)
The purpose of this study is to describe and analyze efforts to empower independent family entrepreneurs in online-based marketing in the Geluran Village environment, Sidoarjo Regency in the middle. The background of this study is in line with social restrictions due to the Covid-19 pandemic, as well as the development of information technology applications for marketing goods and services, so that it is necessary to accelerate the ability of independent family entrepreneurs in online-based marketing. The method used in this study is qualitative descriptive research to describe various online-based marketing efforts ranging from product packaging to product brand development, to online marketing. The results of the study show that in the midst of social restrictions, the need for independent entrepreneurs for online marketing has become a very large demand, for the sake of the continuity of the community's independent entrepreneurship. So that community empowerment in online-based marketing is a necessity that cannot be avoided anymore.